Consumer Behaviour Through Neuromarketing Approach - ALSHARIF, AHMED H.; SALLEH, NOR ZAFIR MD; BAHARUN, ROHAIZAT; YUSOFF, MOHD EFFANDI (The journal of contemporary issues in business and government, 2021)
The advance of neuroscience allowed neuromarketing to use neuroimaging tools, whether for marketing purposes or to study people's daily behaviour. As the main contribution, this review shows how to effectively employ neuroscience tools to understand an individual’s decision-making processes effectively. To this end, we will describe the period of neuromarketing development and its application in evaluating the perception towards marketing stimuli. After that, we will discuss the tools for measuring brain activity and non-brain activity, the pros and cons, what it measures, and when does it use each device. This paper will also discuss a series of publications related to the neuromarketing subject. Moreover, this paper will discuss the ethical issues raised by using these tools to assess human behaviour during purchase decisions. In conclusion, it will be discussed the challenges of this field and the possible future scenario.